(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Legal education is an essential foundation for the sustainability and development of society, ensuring democracy and security by preparing future lawyers, including judges. In an era of rapid digitalization, security issues in legal education are becoming increasingly relevant. Problems such as access to confidential documents, insufficient knowledge of digital security risks, and the lack of protection mechanisms pose significant threats to students, faculty, and lawyers. Addressing these issues is essential to maintain trust in the legal system and ensure the integrity of legal education. The aim of this study is to analyze security aspects in legal education, focusing on the need to improve students' understanding of legal and practical security issues. The study explores how cybersecurity training can be integrated into legal education so that future lawyers acquire the necessary skills to responsibly handle sensitive information in a secure digital environment. The study uses a qualitative research approach that includes a review of the legal framework, academic literature and case studies on cybersecurity challenges in legal education. Comparative analysis is used to examine best practices across jurisdictions regarding security measures in legal studies. In addition, expert opinions from legal professionals and educators are taken into account to assess the effectiveness of current approaches and identify areas for improvement. The results highlight the need to integrate cybersecurity courses into legal education curricula and improve regulatory frameworks to address digital security risks. A more comprehensive approach to legal education that includes practical cybersecurity training would improve students’ ability to navigate ethical and professional challenges in the digital age. Implementing these measures would not only reduce cybersecurity risks, but would also better prepare law students for their professional responsibilities by ensuring their competence in protecting sensitive legal information.